Peningkatan ketahanan suhu dingin kulit atasan sepatu melalui pengurangan daya penyerapan air dan pengaruhnya terhadap sifat fisik dan morfologi - Prayitno Prayitno; Emiliana Kasmudjiastuti (Majalah Kulit, Karet, dan Plastik, 2017)
A research has been undertaken to increase the cold resistance of upper leather by decreasing its water absorption ability. Fluorinated acrylic polymer, a water repellent substance, was added at fatliquoring and finishing stages of upper leather with different concentrations levels. Research findings showed that an increase in the water-repellent concentration, i.e. by 5; 7.5; 10; 12.5; and 15%, result in increases in tensile strength, tearing strength, and elongation at break, whereas decreases in water absorption ability. No significant differences for the other physical properties such as water vapor absorption, water vapor permeability, and flexing resistance and they met the standard for shoe leather. Results of scanning electron microscopy indicated an increased thin layer of water repellent on leather fibers as the water-repellent concentration increased. The leather fibers looked smoother, glistened, and thicker. This indicates the penetration of water repellent onto leather fibers.Keywords: water absorption, water repellent, cold resistance, upper leather.